A Second‐Coordination‐Sphere Strategy to Modulate Nickel‐ and Palladium‐Catalyzed Olefin Polymerization and Copolymerization. (7th August 2017) - Li, Min; Wang, Xingbao; Luo, Yi; Chen, Changle
Abstract: Transition‐metal‐catalyzed copolymerization reactions of olefins with polar‐functionalized comonomers are highly important and also highly challenging. A second‐coordination‐sphere strategy was developed to address some of the difficulties encountered in these copolymerization reactions. A series of α‐diimine ligands bearing nitrogen‐containing second coordination spheres were prepared and characterized. The properties of the corresponding nickel and palladium catalysts in ethylene polymerizations and copolymerizations were investigated. In the nickel system, significant reduction in polymer branching density was observed, while lower polymer branching densities, as well as a wider range of polar monomer substrates, were achieved in the palladium system. Control experiments and computational results reveal the critical role of the metal−nitrogen interaction in these polymerization and copolymerization reactions.